2015
DOI: 10.1111/jog.12778
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pelvic shape among Japanese pregnant women over the last 5 decades

Abstract: The prevalence of the anthropoid-type pelvis have significantly increased in Japan. Identifying a determinant of this phenomenon requires further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The prevalence of the gynaecoid pelvis in this study was found nearly equal to the study conducted on Japanese women with 43.6%. 6 Reduction in the size of the pelvis can lead to morbidity and mortality of the mother and foetus. 7 Variation in pelvic size and shape could be due to daily activities leading to alteration in body mass.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the gynaecoid pelvis in this study was found nearly equal to the study conducted on Japanese women with 43.6%. 6 Reduction in the size of the pelvis can lead to morbidity and mortality of the mother and foetus. 7 Variation in pelvic size and shape could be due to daily activities leading to alteration in body mass.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the anteroposterior diameter/transverse diameter ratio of the pelvis was correlated with operative difficulty. This phenomenon could be attributed to the longer anteroposterior diameter of the pelvic inlet, and the reduced transverse diameter of the outlet might represent the anthropoid-type pelvic shape, which is vertically deeper and transversally narrower than other pelvis types (40). Thus, pelvic inlet incorporated with intertuberous distance might provide clinical measurements for predicting the pelvis with surgical difficulty.…”
Section: Discussionmentioning
confidence: 99%